A localized ELF magnetic field exposure system for microscope cover‐slips. Issue 5 (28th February 2014) - Wang, Paul K. C.
<x xml:space="preserve">Abstract</x> In extremely low frequency (ELF) magnetic field exposure systems for the inverted microscope stage where the cells grown on the entire microscope cover‐slip are exposed to the magnetic field, the effects of variations in cell characteristics from one cover‐slip to another on the experimental data cannot be readily identified. To overcome this drawback, a localized ELF magnetic field exposure system for cells grown on cover‐slips was designed. The basic idea is to expose only a marked portion of the cover‐slip to the magnetic field so that the effect of the ELF magnetic field on the cells grown on the same cover‐slip can be observed under a microscope. A prototype system was built and tested. Experimental test results pertaining to the prototype system performance validate the proposed design approach. The paper concludes with a discussion of alternative approaches to the design of localized ELF magnetic field exposure systems. Bioelectromagnetics. 35:354–362, 2014. © 2014 Wiley Periodicals, Inc.